2020
DOI: 10.47067/real.v3i3.81
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of Students Behaviors and Teachers Attitudes With Corporal Punishment in Peshawar Schools

Abstract: Throughout the world corporal punishment is seen as initial matter. In order to ensure discipline, institutes used corporal punishment as a tool. This study is undertaken in the background of emerging nations particularly Pakistan. It has been observed that on account of corporate punishment in Pakistan mostly students quit educational institutes. The current study discovers the occasion on teacher’s perception regarding corporal punishment across various chosen institutes of KPK. This study targets several we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The findings also showed that teachers were unable to create intrinsic academic motivation in students. According to Sulaiman, et al, (2020), corporal punishment by the teachers compels most of the students (i.e. grade one to ten) to quit their educational institutions in Khyber Pakhtunkhwa.…”
Section: Introductionmentioning
confidence: 99%
“…The findings also showed that teachers were unable to create intrinsic academic motivation in students. According to Sulaiman, et al, (2020), corporal punishment by the teachers compels most of the students (i.e. grade one to ten) to quit their educational institutions in Khyber Pakhtunkhwa.…”
Section: Introductionmentioning
confidence: 99%
“…Benatar (1998, p. 239) argues that it serves a "useful educational purpose". However, while Baumrind (1996), Dlamini et al (2017), Noreen et al (2021), see corporal punishment as a necessary tool for learner discipline, Sulaiman et al (2020) see it as harmful and a practice that causes long-term psychological and physical ill effects.…”
Section: Corporal Punishment As a Means To Discipline Learnersmentioning
confidence: 99%